Pengaruh Implementasi Kerja, Kerjasama Tim Dan Sistem Informasi Manajemen Terhadap Produktivitas Kerja Pegawai Pada Dinas Komunikasi dan Informatika Kabupaten Lingga - Izjumadillah, Izjumadillah; Herman, Hendri (eScience Humanity Journal, 2024)
teamwork, and information system management on employee productivity at the Communication and Information Office of Lingga Regency. The total population in this study consists of 63 employees. The determination of the sample size was done using a saturated sampling technique, which means that all members of the population were used as the research sample. Thus, a total of 63 respondents were obtained as samples. The sampling technique is through probability sampling. Data collection was carried out by distributing questionnaires to the respondents. The collected data was processed using SPSS data processing software. The research findings indicate that, partially, work implementation has an insignificant effect on employee productivity, team collaboration has a significant effect on employee productivity, and information system management has a significant effect on employee productivity. Simultaneously, work implementation, team collaboration, and information system management significantly affect employee productivity. The adjusted R square value is 0.425 or 42.5%. This means that the implementation of work, teamwork, and information system management can explain the work productivity variable by 42.5%. Meanwhile, the remaining 57.5% is explained by other variables that were not included in this research model.